A new species of the genus Paracypria (Crustacea: Ostracoda: Cypridoidea) from the Fiji Islands - Chand, Prerna; Kamiya, Takahiro (Zootaxa, 2016)
A new marine species of the genus Paracypria (Paracypria fijiensis n. sp.) is reported from the Fiji Islands, a small island archipelago in the South Pacific Ocean. This is the first report of a Paracypria species from the Fiji Islands. Descriptions of soft parts and valves of Paracypria fijiensis n. sp. are presented herein, and morphological comparisons are made with existing Paracypria species from Australia, Japan and New Caledonia. Although eight coastal sites were sampled across the Fiji Islands, the new Paracypria species was found at only three sites. Large numbers of P. fijiensis n. sp. were recorded from intertidal flats, indicating it to be highly tolerant of the dynamic intertidal zone conditions.